Cinemedicine: Using movies to improve students' understanding of psychosocial aspects of medicine. (April 2018) - Kadivar, Maliheh; Mafinejad, Mahboobeh Khabaz; Bazzaz, Javad Tavakkoly; Mirzazadeh, Azim; Jannat, Zeinab
Abstract: Background: There are rising concerns about how to teach psychosocial aspects of medicine to students. The aim of the study was the use of "cinemedicine" as a tool and technique in teaching psychosocial aspects of medicine to medical students at Tehran University of Medical Sciences (TUMS). Methods: This was an educational study with quantitative and qualitative data analysis. Two hundred seventy medical students participated in this study. Nine sessions were held to teach psychosocial subjects in medicine using movies. Each session began with an initial explanation of the program objectives. After the show, medicine related points of the movie were discussed and analyzed by experts and students. In the end, questionnaires were distributed to assess the students' perceptions. Results: The results of our study show that most of the students (84%) stated that teaching these subjects through movies was a nice event comparing to usual lectures. 56.5% of the students agreed with the application of points learned in the events in professional performance. The majority of the students (72.8%) agreed that participating in those events was useful for them as a physician and they would advise other students to attend to later sessions. Content analysis of the students' notes uncovered three categories of cinemedicine: "learning by observation", "creation of a supportive and tangible learning" and "motivation for learning". Conclusion: Cinemedicine provides the opportunity for medical students to learn psychosocial subjects related to medicine through observing and reflecting on movies. Highlights: Teaching via movies could be a nicer event in comparison to the usual lecture. Using Cinemedicine as an interactive technique is helpful when educating psychosocial aspects of medicine. Cinemedicine provides the opportunity for medical students to learn via observing and reflecting on movies. The way of running movie session influences the students' learning and motivations.